When the limp has a dietary cause: A retrospective study on scurvy in a tertiary Italian pediatric hospital - Masci, Daniela; Rubino, Chiara; Basile, Massimo; Indolfi, Giuseppe; Trapani, Sandra (Frontiers in Pediatrics, 2022)
The limping child frequently represents a diagnostic challenge. The differential diagnosis is broad and should include vitamin C deficiency.deficiency Scurvy, resulting from vitamin C deficiency, is the oldest-known nutritional disorder. Despite its rarity in developed countries, scurvy has been increasingly reported in recent years in pediatric patients, particularly those with autism or neurological disabilities. In the present retrospective study, we describe the clinical, laboratory and radiological features of 8 patients diagnosed with scurvy in the Pediatrics Unit of Meyer Children's University Hospital, between January 2016 and December 2021. The majority (87%) were males, and the median age was 3.7 years. Half of the patients had comorbidities known to be risk factors for scurvy, while the remaining patients were previously healthy. All the children were admitted for musculoskeletal symptoms, ranging from lower limb pain (87%) to overt limping (87%). Mucocutaneous involvement was observed in 75% cases. Microcytic anemia and elevated inflammatory markers were common laboratory findings. Bone radiographs, performed on all patients, were often interpreted as normal at first, with osteopenia (62%) as the most frequent finding; notably, after re-examination, they were reported as consistent with scurvy in four patients. The most common magnetic resonancemrimaging findings were multifocal symmetrical increased signal on STIR sequence within metaphysese, with varying degrees of bone marrow enhancement, adjacent periosteal elevation and soft tissue swelling. Differential diagnosis was challenging and frequently required invasive diagnostic procedures like bone marrow biopsy, performed in the first three patients of our series. The median time frame between clinical onset and the final diagnosis was 35 days. Notably, the interval times between admission and diagnosis become progressively shorter during the study period, ranging from 44 to 2 days. Treatment with oral vitamin C led to improvement/resolution of symptoms in all cases. In conclusion, scurvy should be considered in the differential diagnosis in a limping child, performing a detailed dietary history and careful physical examination, looking for mucocutaneous lesions. A quick and correct diagnostic path avoids invasive diagnostic procedures and reduces the risk of long-term complications.